Measuring the users and conversations of a vibrant online emotional support system - Calzarossa M.C.; Massari L.; Doran D.; Yelne S.; Trivedi N.; Moriarty G. (My University, 2025)
Online social systems have emerged as a popular medium for people in society to communicate with each other. Among the most important reasons why people communicate is to share emotional problems, but most online social systems are uncomfortable or unsafe spaces for this purpose. This has led to the rise of online emotional support systems, where users needing to speak to someone can anonymously connect to a crowd of trained listeners for a one-on-one conversation. To better understand who, how, and when users utilize emotional support systems, this paper examines user and conversation characteristics on 7 Cups of Tea. 7 Cups of Tea is a massive, vibrant emotional support system with a community of listeners ready to help those with any number of emotional issues. Intriguing insights, including evidence of world-wide adoption of the service, the need to seek immediate support from many others, and a rich-get-richer phenomenon underscore a growing need for online emotional support systems and highlight important aspects to promote their long-term viability. © 2016 IEEE.